THE INFLUENCE OF THE BIG FIVE PERSONALITY ON FEAR OF MISSING OUT ON PROMOTIONAL CONTENT ON INSTAGRAM @giladiskonn - Vincent Giovanni; Lasmery R. M. Girsang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The development of technology and information in Indonesia is very rapid which has made internet and social media users in Indonesia continue to experience a very significant increase. The diversity and convenience provided by the internet makes its users experience an increase in the time they access it and always have the desire to check their social media accounts, one of which is Instagram social media. This phenomenon is often called the Fear of Missing Out (FoMO). FoMO is a fear, discomfort, always wanting to know other people's activities, and a feeling of missing moments that arises in an individual. FoMO can make an individual's behavior focus only on the outside world, thus making him lose his identity and focus more on others than himself. This can become an anxiety and fear that will affect the personality of its users or can be called the big five personality. The Indonesian people are also very enthusiastic about finding information related to promotions, so one of the accounts, @giladiskonn, uses this, which provides information about culinary promos, traveling, fashion, and others. Based on this, the researcher conducted a study to find out whether there was an influence of the big five personality on Fear of Missing Out on social media Instagram @giladiskonn. This research method is quantitative and collects data from questionnaires distributed via Instagram to followers of @giladiskonn. Then the data is processed in SPSS version 25 for windows and the results show that there is a significant influence of the big five personality on the fear of missing out on promotional content @giladiskonn.